Determination of the biological effects of «Trifuzol-H», «Trifuzole suspension» and «Trifuzole solution for injection» - Киричко, Б. П.; Звенігородська, Т. В.; Парченко, В. В.; Гиренко, І. В. (Scientific Progress & Innovations, 2017)
It is established that the use of «trifuzol-H» in the blood serum of rats increases the activity of the alanine aminotransferase (p<0,001), increases the creatinine content (p<0,05), decreases the uric acid content (p<0,05) and the gamma-glutamyltranspeptidase activity (p<0,05). With the use of the drug «trufuzole suspension», the activity of aspartate aminotransferase (p<0,01) and lactate dehydrogenase (p<0,05), uric acid content decreases (p<0,01), creatinine content increases (p<0,05). With the use of the drug «trufuzole injectable solution», the activity of lactate dehydrogenase (p<0,05) and gamma-glutamyltranspeptidase (p<0,05), cholesterol (p<0,05), triglycerides (p<0,05) and the creatinine content increases (p<0,05).